Effects of the Parental Sensitivity Intervention Among Mothers and Fathers of Preterm Infants: A Quasi-Experimental Study - Phianching, Kulwara; Chaimongkol, Nujjaree; Pongjaturawit, Yunee (Pacific Rim International Journal of Nursing Research, 2020)
Infants who are born prematurely or of a gestational age less than 37 weeks with birth weight less than 2500gramsusually require long hospitalizations in order to receive highly specialized care,resulting in separation from their parents.This separation may have negative consequences on the development of a healthy attachment between parents and their babies.In addition,due to the fragility of preterm infants,parents often lackconfidence tocare for them.This study aimed to examine the effects ofa parental sensitivity intervention on attachment and confidence/self-efficacy among mothers and fathers of preterm infants.A convenience sampling was used to recruit 34 triads of mothers, fathers and preterm infants with 17 triads in each group.The Postpartum Bonding Questionnaire and the Maternal Confidence Questionnaire were used to measure attachment andself-efficacy at three pointstime(Baseline, Day3 and Day7).The experimental group received four sessions of 1)teaching infant states and cues, 2)observing the mothers’state-modulation and cue-reading skills,3)checking the mothers’state-modulation and cue-reading skills,and4)providing parental support, and routine care while the control group received only the routine care at the hospital. Repeated measure ANOVAs were used to analyze the data. The results revealed that father-infant attachment and self-efficacy were significantly higher in the intervention group compared to the control group at post-intervention of Day3 and Day7.However, mother-infant attachment and self-efficacy were not significantly different between the experiment and the control group.These findings suggest the benefit of a parental sensitivity intervention,especially for fathers of preterm infants.Nurses should utilize this intervention to educate the parents of preterm infants,focusing on both mother and father,before the baby is discharged from hospital.